Impact of Pre-existing NS5A-L31 or -Y93H Minor Variants on Response Rates in Patients Infected with HCV Genotype-1b Treated with Daclatasvir/Asunaprevir. Issue 7 (July 2016) - Hernandez, Dennis; Yu, Fei; Huang, Xin; Kirov, Stefan; Pant, Saumya; McPhee, Fiona
Abstract Introduction The combination of daclatasvir (DCV, pan-genotypic NS5A inhibitor) plus asunaprevir (ASV; NS3 protease inhibitor) is approved in Japan, Korea and other countries for the treatment of chronic hepatitis C virus (HCV) genotype (GT)-1. A high ( 90 to 100%) sustained virologic response (SVR) with DCV/ASV therapy has been achieved by excluding patients infected with HCV GT-1b with baseline NS5A resistance-associated variants (RAVs) at L31 or Y93H detected by direct sequencing (DS). We set out to determine whether patients with minor variants at NS5A-L31 or -Y93H, detected by next-generation sequencing (NGS), impacted SVR rates with DCV/ASV therapy. Methods Baseline samples from 222 interferon (IFN)-ineligible/intolerant (N = 135) and prior non-responder (N = 87) patients infected with GT-1b who were treated with DCV/ASV for 24 weeks in the Phase 3 clinical study AI447026 were prepared for NGS (Ion-Torrent platform). The prevalence of baseline NS5A RAVs and their impact on SVR when observed at ≥1% by NGS in a patient's virus population were examined. NGS and DS (sensitivity ≥20%) data were compared. Results The prevalence of baseline NS5A RAVs at L31 or Y93H was 29% (63/219) and 18% (39/214) by NGS and DS, respectively. SVR24 rates were comparable in patients without observed baseline L31 or Y93H polymorphisms whether assessed by NGS (96%; 148/154) or by the less sensitive DS platform (95%; 164/173). Conclusion Optimal SVR rates (≥95%) to DCV/ASV treatment were achieved using DS to exclude patients infected with GT-1b with NS5A RAVs at L31 or Y93H representing ≥20% of their virus population. Exclusion by NGS of patients with minor variants in NS5A (<20%) did not enhance SVR rates. These results suggest that the presence of minor variants in NS5A does not appear to impact the overall SVR rate in patients with GT-1b treated with DCV/ASV. Funding This study was sponsored by Bristol-Myers Squibb. Trial registration ClinicalTrials.gov identifier: NCT01497834.